Strategi pengembangan usaha peternakan babi Di Kabupaten Malang - Ariani Trisna Murti; Karunia Setyowati Suroto; Heri Samba Dima (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2021)
The research conducted at PT. Farm Delta Peniwen Makmur which is located in Peniwen Village, Kepanjen District, Malang Regency for a month in July – August 2020. The research objectives are 1. To find out the strategy for developing pig farming business at PT. Farm Delta Peniwen Makmur Kepanjen Malang, 2. To find out what factors influence the development of pig farming at PT. Farm Delta Peniwen Makmur Kepanjen Malang 3. To find out the position of the business when viewed from the pig farming strategy at PT. Farm Delta Peniwen Makmur Kepanjen. Primary data is obtained from interviews with respondents, while secondary data is obtained from reports from companies and related agencies, literature owned by companies, and writings related to the topics discussed. The sampling method used total sampling, namely owners, managers, and employees of PT. Delta Peniwen Makmur in Kepanjen, Malang. The interview process uses a list of questions in the form of a questionnaire. The data analysis method uses SWOT analysis, namely analyzing the IFE matrix, EFE matrix, IE matrix and SWOT matrix. The conclusion that can be drawn from the results of the analysis is that in the SWOT matrix, the WT strategy is the most dominant in quadrant IV, which is 1.4 with the results of the IFAS and EFAS calculations on the Cartesian diagram (–0.249 ;–0.164). The company seeks to minimize weaknesses and avoid threats by improving product quality, human resources, production quantities, owners can be responsible for all decisions, carry out innovative promotions, provide maximum service at affordable prices, maintain good relations with distributors or customers regarding complaints that arise. exist, and companies can seek market opportunities in different areas. Suggestions that can be quoted from the conclusion are that companies can further maximize existing strengths and opportunities such as maintaining good relationships with employees, agents and customers, expanding marketing areas by conducting digital promotions, improving production quality, providing affordable prices along with price discounts, and no less important being able to establish relationships with competitors to grow the economy of the surrounding community. Keywords: Development Strategy, Livestock Business, Pig Farming